Evaluación de la administración de justicia penal peruana y propuesta del modelo integral garantista - Aredo Córdova, Ricardo Amílcar (2009)
ABSTRACT In this investigation, has been examinated the administration of the peruvian penal justice by analyzing the penal process models and the legal procedures used in the juridical normativity and it has been designed a model called “an integral guarantist penal process model” as an alternative to the models presently in force. The applied penal process models and their juridic normativity since the colonial epoch up now (about five centuries) have been evaluated and reformulated some basic notions of the administration of penal justice and integrating their components by taking as reference the national empirical reality (specially the socio-economical one), the legitimate interests of the great majority of people of the country and the democratic- juridic principles of the right and justice in its integral and guarantist context (legal juridic or formal, sociological and axiological). Surveys have been prepared and applied to university teachers, magistrates, lawyers and citizens in general and it has been examined the statistic information of processal loads and penal documents in draft and solved of the superior courts of Justice of La Libertad, Huaura and others. Among other things, it was found that the applied processal models and the juridic normativity have been found unsuitable and unconvenient in the administration of the Peruvian penal justice and that the proposed alternative model meaningfully improves quantitative and qualitatively the applied models, overcoming the benefts of the model admitted in the New Processal Penal Code of 2004.